Quantitation of resistance training using the session rating of perceived exertion method - Sweet, T. W.; Foster, C.; McGuigan, M. R.; Brice, G. (The Journal of Strength and Conditioning Research, 2004)
The purpose of this study was to apply the session rating of perceived exertion (RPE) method, which is known to work with aerobic training, to resistance training. Ten men (26.1 ± 10.2 years) and 10 women (22.2 ± 1.8 years), habituated to both aerobic and resistance training, performed 3 × 30 minutes aerobic training bouts on the cycle ergometer at intensities of 56%, 71%, and 83% VO2 peak and then rated the global intensity using the session RPE technique (e.g., 0-10) 30 minutes after the end of the session. They also performed 3 × 30 minutes resistance exercise bouts with 2 sets of 6 exercises at 50% (15 repetitions), 70% (10 repetitions), and 90% (4 repetitions) of 1 repetition maximum (1RM). After each set the exercisers rated the intensity of that exercise using the RPE scale. Thirty minutes after the end of the bout they rated the intensity of the whole session and of only the lifting components of the session, using the session RPE method. Results and conclusion: The rated intensity of exercise increased with the %VO2 peak and the %1RM. There was a general correspondence between the relative intensity (%VO2 peak and % 1RM) and the session RPE. Between different types of resistance exercise at the same relative intensity, the average RPE after each lift varied widely. The resistance training session RPE increased as the intensity increased despite a decrease in the total work performed (p < 0.05). Mean RPE and session RPE-lifting only also grew with increased intensity (p < 0.05). In many cases, the mean RPE, session RPE, and session RPE- lifting only measurements were different at given exercise intensities (p < 0.05). The session RPE appears to be a viable method for quantitating the intensity of resistance training, generally comparable to aerobic training. However, the session RPE may meaningfully underestimate the average intensity rated immediately after each set.